Hubungan kerohanian di tempat kerja dan keberkesanan pengajaran guru Maktab Rendah Sains Mara - Rosmaini Irsham, Romli (2021)
The Education plays an important role in the development of a country. In line with that, the MARA Science Junior College (MRSM) was established to provide educational facilities at the secondary level in science and technology to bumiputera students who have high academic and intellectual abilities to develop their potential. However, the vision and mission of the establishment of MRSM will not be successful if the spirituality of the educators is not focused. Therefore, this study was conducted to identify the relationship between spirituality and teaching effectiveness among MRSM teachers in the state of Penang. A total of 134 MRSM teachers were involved in this study using the survey method. The research instrument for spirituality in the workplace was adapted from Ashmos and Dunchon (2000). The teaching effectiveness instrument was adapted from Ansari, Achoui and Ansari (2000). Data were analyzed using descriptive and inferential statistics applying t-test, ANOVA, Pearson correlation and multiple regression. The findings of the study found that there is a significant relationship between spirituality in the workplace with the teaching effectiveness of teachers. Multiple regression tests found that the internal dimensions and conditions or feelings of the community had a positive effect on the teaching effectiveness of MRSM teachers in the state of Penang. Studies show that the level of spirituality influences the teaching effectiveness of an educator in school. Therefore, in order to improve the effectiveness of teachers' teaching, programs of a spiritual nature need to be enhanced in addition to other professional development programs.